A study of particulate matter concentration released during laser paint removal process on car coated substrate - Mohammad Khairul Azhar Abdul Razab; Mohamad Suhaimi Jaafar; Azhar Abdul Rahman (2014)
Normalization mass (N) of particulate matter (PM) per one laser shot and 1.0 cm2